Step * 1 1 1 of Lemma accelerate-real-strong-regular


1. : ℕ+
2. : ℕ+ ⟶ ℤ
3. ∀n,m:ℕ+.  (|(m (x n)) (x m)| ≤ ((2 1) (n m)))
4. : ℕ+
5. : ℕ+
6. |2 k|
7. ∀a:ℤ(|a rem k| ≤ ((2 k) 1))
8. : ℤ
9. (x ((2 k) n) rem k) v ∈ ℤ
10. |v| ≤ ((2 k) 1)
11. v1 : ℤ
12. (x ((2 k) m) rem k) v1 ∈ ℤ
13. |v1| ≤ ((2 k) 1)
14. |(((2 k) m) (x ((2 k) n))) ((2 k) n) (x ((2 k) m))| ≤ ((2 1)
    (((2 k) n) ((2 k) m)))
⊢ (|(m (x ((2 k) n))) (x ((2 k) m))| |(n v1) v|) ≤ (((2 k) 1) (n m))
BY
((Subst' (((2 k) m) (x ((2 k) n))) ((2 k) n) (x ((2 k) m)) (2 k)
    ((m (x ((2 k) n))) (x ((2 k) m))) -1
    THENA Auto
    )
   THEN (RWO "absval_mul" (-1) THENA Auto)
   THEN (Subst' |2 k| -1 THENA Auto)
   THEN (Assert |(m (x ((2 k) n))) (x ((2 k) m))| ≤ (2 (n m)) BY
               (Mul ⌜k⌝ 0⋅ THEN Auto))) }

1
1. : ℕ+
2. : ℕ+ ⟶ ℤ
3. ∀n,m:ℕ+.  (|(m (x n)) (x m)| ≤ ((2 1) (n m)))
4. : ℕ+
5. : ℕ+
6. |2 k|
7. ∀a:ℤ(|a rem k| ≤ ((2 k) 1))
8. : ℤ
9. (x ((2 k) n) rem k) v ∈ ℤ
10. |v| ≤ ((2 k) 1)
11. v1 : ℤ
12. (x ((2 k) m) rem k) v1 ∈ ℤ
13. |v1| ≤ ((2 k) 1)
14. ((2 k) |(m (x ((2 k) n))) (x ((2 k) m))|) ≤ ((2 1) (((2 k) n) ((2 k) m)))
15. |(m (x ((2 k) n))) (x ((2 k) m))| ≤ (2 (n m))
⊢ (|(m (x ((2 k) n))) (x ((2 k) m))| |(n v1) v|) ≤ (((2 k) 1) (n m))


Latex:


Latex:

1.  k  :  \mBbbN{}\msupplus{}
2.  x  :  \mBbbN{}\msupplus{}  {}\mrightarrow{}  \mBbbZ{}
3.  \mforall{}n,m:\mBbbN{}\msupplus{}.    (|(m  *  (x  n))  -  n  *  (x  m)|  \mleq{}  ((2  *  1)  *  (n  +  m)))
4.  n  :  \mBbbN{}\msupplus{}
5.  m  :  \mBbbN{}\msupplus{}
6.  2  *  k  \msim{}  |2  *  k|
7.  \mforall{}a:\mBbbZ{}.  (|a  rem  2  *  k|  \mleq{}  ((2  *  k)  -  1))
8.  v  :  \mBbbZ{}
9.  (x  ((2  *  k)  *  n)  rem  2  *  k)  =  v
10.  |v|  \mleq{}  ((2  *  k)  -  1)
11.  v1  :  \mBbbZ{}
12.  (x  ((2  *  k)  *  m)  rem  2  *  k)  =  v1
13.  |v1|  \mleq{}  ((2  *  k)  -  1)
14.  |(((2  *  k)  *  m)  *  (x  ((2  *  k)  *  n)))  -  ((2  *  k)  *  n)  *  (x  ((2  *  k)  *  m))|  \mleq{}  ((2  *  1)
        *  (((2  *  k)  *  n)  +  ((2  *  k)  *  m)))
\mvdash{}  (|(m  *  (x  ((2  *  k)  *  n)))  -  n  *  (x  ((2  *  k)  *  m))|  +  |(n  *  v1)  -  m  *  v|)  \mleq{}  (((2  *  k)  +  1)
    *  (n  +  m))


By


Latex:
((Subst'  (((2  *  k)  *  m)  *  (x  ((2  *  k)  *  n)))  -  ((2  *  k)  *  n)  *  (x  ((2  *  k)  *  m))  \msim{}  (2  *  k)
    *  ((m  *  (x  ((2  *  k)  *  n)))  -  n  *  (x  ((2  *  k)  *  m)))  -1
    THENA  Auto
    )
  THEN  (RWO  "absval\_mul"  (-1)  THENA  Auto)
  THEN  (Subst'  |2  *  k|  \msim{}  2  *  k  -1  THENA  Auto)
  THEN  (Assert  |(m  *  (x  ((2  *  k)  *  n)))  -  n  *  (x  ((2  *  k)  *  m))|  \mleq{}  (2  *  (n  +  m))  BY
                          (Mul  \mkleeneopen{}2  *  k\mkleeneclose{}  0\mcdot{}  THEN  Auto)))




Home Index